An electro-optical simulator for eLISA LOT: Lisa On Table. (April 2015) - Gruning, P; Halloin, H; Brossard, J; Prat, P; Baron, S; Buy, C; Jimenez, P
Abstract: This paper describes the progress on a hardware simulator of eLISA developed at the APC laboratory in Paris, France. It is designed to simulate realistic noise and the appropriate delays resulting from the huge distances the laser has to travel between the eLISA spacecrafts. We present the experimental setup consisting of an optical and electric interferometer. Also, the time delay interferometry noise reduction method and its performance on simulated signals in the simplest transponder case will be described.